Agricultural waste to energy : a case study of Nakhon Si Thammarat Province - Surachet Yanwaree; Salam, Abdul P.; Kumar, Sivanappan; Dhakal, Shobhakar; Asian Institute of Technology Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2014)
Nakhon Si Thammarat province is in the South of Thailand. The majority of the people in this province work in agriculture; they are plantation, fishery and livestock. Although, lot of agricultural residues and fishery wastes are available, much of them are wasted and not used for energy purpose. This study illustrates the potentials of agriculture wastes and suggests technologies for converting waste to energy. Agriculture wastes in the province can be separated into three types that are agricultural residues, animal wastes and wastes from marine shrimp farming. Agricultural residues considered in this study are residues from paddy, Para tree, Coconut, oil palm, durian, rambutan, mangosteen and longkong. Six residues with high potential for energy are dry leaves of Para tree, frond of oil palm, paddy straw, Para wood slab, oil palm male bunches and paddy husk. Theoretical energy potentials of those six residues are estimated to be 16,800 TJ/year, 115 TJ/year, 3,700 TJ/year, 780 TJ/year, 840 TJ/year and 560 TJ/year, respectively. Animal wastes from buffalo, cattle, swine, chicken, duck and goat are studied. Three animal wastes of the most theoretical energy potential are wastes from cattle, swine and chicken. Theoretical energy potentials of those wastes are around 130 TJ/year, 160 TJ/year and 37 TJ/year, respectively. Theoretical energy potential of marine shrimp sediment is estimated to be 780 GJ/year. Trends of agriculture wastes are also studied. The trends of amount of plantation area and production directly affect the trend of energy potential in the future, moreover, government policy, economics, climate change, natural disaster, pestilence and increasing of population cause changing of amount of these wastes. Agricultural wastes considered for suggesting suitable technology for converting to energy are paddy husk, swine wastes and shrimp farm sediment. Paddy husk is used to be fuel in combustion technology and gasification technology. The paddy mills are classified into three types that depend on distance location and two cases based on time operation. Gasification is suitable for two plants that install within 25 km radius of mills, both power plants operate in peak time period. Combustion and gasification technologies are suitable for plants installation within 100 km radius of mills, operation time of the gasification and the combustion power plant should bein peak times and all day, respectively. However, paddy husk cost directly affects the benefit and costs of power plants in all cases. 58 swine farms of medium size are studied. Anaerobic digestion technologies in the analysis are Covered lagoon and UASB. Swine farms that have number of swine 140 to 580 livestock units are suitable for electricity application, and the swine farms that are swine capacity between 40 and 130 livestock units should be used for heating utilization. Treatment land used is one factor that is importance to decide digester installation. Anaerobic digestion system using shrimp pond sediment was studied and found that the system is not suitable for installation because the biogas generation capacity is low.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Energy
Thesis (M.Eng.) - Asian Institute of Technology, 2014
Keywords: Agricultural wastes -- Thailand -- Nakhon Si Thammarat; Biomass energy -- Thailand -- Nakhon Si Thammarat